ANALISIS DAMPAK PENGUNGKAPAN AKUNTANSI LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Devi Lia; Ersi Sisdianto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to analyze the impact of environmental accounting disclosure on firm value. Environmental accounting is an integral part of sustainability practices that has become increasingly significant amidst growing public and investor awareness of environmental issues. The data used in this study are secondary data from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) over a specific period. Environmental accounting disclosure is measured using the environmental disclosure index based on the Global Reporting Initiative (GRI) guidelines, while firm value is measured using Tobin’s Q ratio. This research employs multiple linear regression to examine the relationship between environmental accounting disclosure and firm value, considering control variables such as firm size, profitability, and leverage. The results indicate that environmental accounting disclosure has a positive and significant effect on firm value. These findings suggest that companies actively disclosing environmental information receive greater market appreciation, as reflected in increased firm value. This study is expected to contribute to the development of environmental accounting literature and provide insights for companies to enhance their value through sustainable practices.